2010
DOI: 10.1002/chp.20067
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in Pennsylvania: Rapidly spreading improved chronic care for patients to practices

Abstract: Early data reporting, practice preparation for the first learning session, monthly narrative reports from practices, and clear and concrete change packages all seem integral to the improvement process. The future of the PA Chronic Care Initiative will include spreading to more practices and moving beyond the initial work in diabetes and asthma to other aspects of primary care, including prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 2 publications
2
33
0
Order By: Relevance
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 61%
“…Several case studies have demonstrated that education, specifically Performance Improvement (PI) CME, improves clinical practice. [28][29][30][31][32][33][34][35] However, to our knowledge, data do not exist regarding the use of the PI CME format in the specialty of dermatology. PI CME helps physicians evaluate their practice and implement evidencebased strategies to overcome identified gaps, then remeasure their performance after these strategies have been implemented in their practice.…”
mentioning
confidence: 61%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Accordingly, we leveraged a large sample of small to medium-size primary care practices in the United States to (1) assess the extent to which they use QI strategies as measured by the Change Process Capability Questionnaire (CPCQ) Strategies Scale, and (2) evaluate practice characteristics and contextual factors that may explain variations in use of QI strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has yielded unclear results regarding the effectiveness of QI initiatives at improving diabetes care, showing positive change in clinical process measures and intensification of medication but no change in clinical outcomes. 36,[42][43][44] Recent chart audit studies showed inconsistent improvement in A1c, BP, and LDL, depending on the length of the period after the initiative. 16,[45][46][47] This study had a relatively short period after the program (1 year), yet significant improvements were found.…”
Section: Discussionmentioning
confidence: 99%
“…31 In terms of QI methodologies, the program embraced the Institute for Healthcare Improvement's Breakthrough Series approach 32 of bringing multiple teams together 2 or 3 times (ie, learning sessions) over 6 to 15 months to learn from experts, and each other, as they plan and test practice changes. 32,36 Furthermore, this approach encourages team members who attend learning sessions, usually 2 or 3 people, to work with additional team members in their organization to test and implement changes between the learning sessions (ie, action periods). Lastly, the program embedded the Model for Improvement as a strategy to test and evaluate changes on a few patients before implementing them at a practice or organizational level.…”
Section: Introductionmentioning
confidence: 99%